Ecological Determinants of Nest-Site Selection by a Keystone Engineer : the Red-naped Sapsucker - Lowney, Jessica (My University, 2010)
Woodpeckers are considered keystone engineers because they excavate nest cavities that ultimately provide shelter for other species. In aspen woodlands of the Rocky Mountains, red-naped sapsuckers are the predominant woodpecker, providing nest holes for multiple bird species. Sapsuckers also create sap wells in willows thus supplying a food resource for many species. Conserving sapsuckers and the associated community requires that we understand sapsucker habitat requirements. Our research conducted in the East River Valleyof Colorado during 2007-2008, which compared sites with sapsucker nests to those without, found that nest sites had more surrounding willow and more aspen heartrot fungus, which promotes nest excavation. In 2009, we began sampling randomly selected points inthe ERV in order to better understand the relationship among the fungus, willow, and other variables.
Color poster with text and images.
Keywords: Red-naped sapsucker; Woodpeckers--Habitat; Woodpeckers--Nests; Forest ecology; Posters